25 years of operation of the Program of Interlaboratory Rounds for Food Analysis (PRIDAA): Contributions to the evaluation of the performance of chemical food analysis laboratories in Latin America - Lois-Martínez, Mónica (2024)
The Food Analysis Interlaboratory Rounds Program (PRIDAA) was designed and developed between 1998 and 2023 by the National Center for Food Science and Technology (CITA) at the University of Costa Rica to provide an accessible proficiency testing program in food chemistry for Latin American laboratories. The program operated regularly during this period, with four to five rounds per year covering five food groups: cereals and derivatives, fruits and derivatives, dairy, meat or fish products, and roasted coffee, aimed at evaluating analyses of nutritional components or quality parameters. The program’s design was based on ISO/IEC Guide 43:1 and the “International Harmonized Protocol for Proficiency Testing of (Chemical) Analytical Laboratories” developed by IUPAC/ISO/AOAC, later adopting INTE/ISO/IEC 17043:2013 as the reference standard for program accreditation by the Costa Rican Accreditation Entity, obtained in 2020. Over its 25 years of operation, PRIDAA completed 108 rounds with the participation of 91 laboratories across 16 Latin American countries. The participant profile consisted of 54 % institutional laboratories, 24 % private service laboratories, and 22 % quality control laboratories from food industries. The countries with the highest participation were Costa Rica, Guatemala, and Ecuador, accounting for 56 % of the laboratories involved. The results obtained over these years primarily provided feedback to participants for performance improvement, but they also allowed identification of the analyses in which laboratories demonstrated stronger overall performance and the more complex tests to achieve satisfactory results. The preparation process for accreditation led to enhancements in the calculation methodologies used, facilitating statistical analysis and decision-making, and ensuring reliable results for participating laboratories.